102. Address the dosimetry in radiometabolic therapy; relationship between dosimetric value and clinical parameters in differentiated thyroid cancer. (December 2018) - Rossi, G.; Scaccia, L.; Busonero, G.; Capoccetti, F.; Camarda, M.; Bartolozzi, C.; D'Avenia, P; Dente, AM; Di Nicola, E.; Gasparrini, N.; Fattori, S
Abstract : Purpose: Use rationally the Red Marrow (RM) and Whole Body (WB) dosimetry pre and during therapy in Differentiated Thyroid Cancer (DTC) focalinzing the relationship between clinical parameters. Methods: We enrolled 120 patients (278 dosimetries-196 with complete clinical data) with DTC (March 2012–December 2017). We made double dosimetric study the week before the therapy (19 MBq 131I) and during therapy (range 1019–9342 MBq, mean 6253 MBq, median 6208 MBq), collecting serial blood samples and WB counts according to the AIFM Italian dosimetric protocol and EANM SOP. With a simple regression analysis, we studied the capability of residence times (tau) and mGy/MBq (RM and WB) to predict the respective post therapy values (Fig. 1). We moreover considered a multivariate multiple regression model to control for clinical values (sex, age, histology, variant, multifocality, bilaterality, Tsh Ipo, Tg Ipo, FT4, staging and another tumour). Results: All the variables pre-treatment have a significant role in explaining the levels of the corresponding variables post-treatment (Fig. 1). For all the variables, a PRE unitary increase determines a much smaller increase in post values (from 0.3 to 0.5). When considering all the variables as possible predictors (Table 1), none of them seems to have an effect on WBposttau, apart from WBpretau. For RMposttau, instead, we found correlation with RMpretau, WBpretau, age and the presence of another tumour. Concerning WBpostmGyMBq and RMpostmGyMBq, both appear to be reduced for N1b staging; WBpostmGyMBq reduced for advanced tumours and increased for large values of WBpretau. RMpostmGyMBq increases with age and RMpretau. A large parte of the total variability of WBpostmGyMBq and RMpostmGyMBq remains unexplained. Conclusions: Dosimetry connected with clinical values could be a useful tool to help in patient management to predict behaviour and efficacy. Mandatory next step is to study follow up.